When and How Zdeněk Nejedlý Parted Company with the Goll School - Havelka, Miloš (Dějiny – teorie – kritika, 2010)
This study distinguishes four stages in the development of Nejedlý’s historical work: positivist student, philosophizing historian, left-wing „realist“ and „awakener“ of a „socialist“ nation. It highlights a detailed analysis of Nejedlý’s arguments typifying the transition from the second to the third stage, which is characterized in this paper as a departure from the scientifi c principles of the „Goll school“. Th is period is typifi ed by Nejedlý’s paper On the Meaning of Czech History (1913) and Th e End of Liberalism in Historiography (1921), in which Nejedlý bases himself both on Masaryk’s criticism and on his own interpretation of socialist ideas and liberalism. For his rejection of „Goll’s historiography“ and his objectivistic maxims, he devises the term „historical liberalism“, which he believes is supposedly based on the superfi cial „liberalism“ of historical knowledge. However, it turns out that neither in the third nor the fourth stage of his intellectual development was Nejedlý a Marxist as the term was understood at that time, but rather a belated socialist-oriented national „awakener“.